KESUKSESAN IMPLEMENTASI INOVASI ORGANISASI - Thawil, Sitti Marijam; Sari, Santi Retno (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
Innovation is very important for the competitive advantage of organizations to survive severe global competition and the rapidly changing business environment. Organizations or companies must be more innovative to grow, develop, and have competitive advantages and make profits. The success of innovation for the organization lies not only in the right decision to adopt innovation but more importantly in the implementation of innovation. Although there has been a lot of literature discussing innovation, it is still lacking which addresses the implementation of innovation. The present study aims to contribute to existing implementation literature by, first, the key factors of successful innovation implementation. Second, the process of implementing innovation. Third, the strategic aspect of the implementation of innovation. Fourth, discussing innovations that will be different at several levels or multi levels and types and social networks. Keywords: organizational innovation